Fabrication and characterization of BaTiO3-Ni0.8Zn0.2Fe2O4-B2O3-Na2O-SiO2multiferroic glass ceramics - Pratthana Intawin (2018)
Copyright © 2016 American Scientific Publishers All rights reserved. Multiferroic glass ceramics from Ni0.8Zn0.2Fe2O4-BaTiO3-Na2O-B2O3-SiO2system have been fabricated and characterized by conventional melt quenching method. In order to change the fabricated glass to glass ceramic samples, a heat treatment technique was employed using temperatures ranging between 600 and 900°C for 2 h. Glass transition and crystallization temperatures were investigated by differential thermal analysis. The X-ray diffraction patterns showed the presence of the amorphous phase and the precipitation crystalline phase in the amorphous matrix. The morphology of the crystals was studied by scanning electron microscope. It was found that the crystal size and crystallinity increased with increasing heat treatment temperature, which also played an important role in controlling the properties of the glass ceramics, including physical, magnetic, dielectric and ferroelectric properties.